2023
DOI: 10.1080/20008066.2023.2202058
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and day-to-day PTSD symptom variability: an ecological momentary assessment and actigraphy monitored study in trauma-exposed young adults

Abstract: Background: Disrupted sleep and post-traumatic stress disorder (PTSD) are bi-directionally linked and have been found to mutually reinforce each other on a day-to-day basis. However, most of the previous research has focused on subjective measures of sleep only. Objective: Here, we investigated the temporal relationship between sleep and PTSD symptoms using both subjective (sleep diary) and objective measures of sleep (actigraphy). Methods: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…Men, 7. Women 12 qualitative or quantitative empirical study using child or adult clinical or non-clinical samples and presented CPTSD separated by gender or sex, or in one gender or sex only Yes Mellor et al ( 2021 ) Systematic review Gender (male, female); how measured is not explicitely stated 13 empirical studies in refugee and displaced treatment seeking or general populations No Nordström et al ( 2022 ) Cross-sectional (based on the fourth data collection eight years after the Utøya terror attack) Gender (male, female) 88 bereaved parents and 34 siblings aged 19 and above (59.8% female, Norway) Yes Pociunaite et al ( 2023 ) Longitudinal data from the data-archive of the Measurement Archive of Reactions to Bereavement from Longitudinal European Studies (MARBLES) project Gender (male, female) 398 bereaved adults (64.2% female, Denmark & The Netherlands) No Rasmusson et al ( 2018 ) Cross-sectional Gender (male, female) 112 patients in treatment for substance use disorders and 112 matched controls with mild to moderate mental health disorders (each group 43.8% female, Norway) Yes Schenker et al ( 2023 ) Cross-sectional Sex, biologically (use both male, female and men, women; none of the participants indicated their sex as ‘other’) 41 non-treatment seeking, trauma exposed young adults aged 18–50 years (75.6% female, Australia) Yes Søegaard et al ( 2021 ) Cross-sectional Self-reported gender (men, women) 110 traumatized patients attending a mental health outpatient clinic (61.8% female, Norway) Yes Stelzer et al ( 2019 ) Cross-sectional Gender (men, women) 50 bereaved widow(er)s and parents (58% female; USA) ...…”
Section: In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Men, 7. Women 12 qualitative or quantitative empirical study using child or adult clinical or non-clinical samples and presented CPTSD separated by gender or sex, or in one gender or sex only Yes Mellor et al ( 2021 ) Systematic review Gender (male, female); how measured is not explicitely stated 13 empirical studies in refugee and displaced treatment seeking or general populations No Nordström et al ( 2022 ) Cross-sectional (based on the fourth data collection eight years after the Utøya terror attack) Gender (male, female) 88 bereaved parents and 34 siblings aged 19 and above (59.8% female, Norway) Yes Pociunaite et al ( 2023 ) Longitudinal data from the data-archive of the Measurement Archive of Reactions to Bereavement from Longitudinal European Studies (MARBLES) project Gender (male, female) 398 bereaved adults (64.2% female, Denmark & The Netherlands) No Rasmusson et al ( 2018 ) Cross-sectional Gender (male, female) 112 patients in treatment for substance use disorders and 112 matched controls with mild to moderate mental health disorders (each group 43.8% female, Norway) Yes Schenker et al ( 2023 ) Cross-sectional Sex, biologically (use both male, female and men, women; none of the participants indicated their sex as ‘other’) 41 non-treatment seeking, trauma exposed young adults aged 18–50 years (75.6% female, Australia) Yes Søegaard et al ( 2021 ) Cross-sectional Self-reported gender (men, women) 110 traumatized patients attending a mental health outpatient clinic (61.8% female, Norway) Yes Stelzer et al ( 2019 ) Cross-sectional Gender (men, women) 50 bereaved widow(er)s and parents (58% female; USA) ...…”
Section: In This Special Issuementioning
confidence: 99%
“…Schenker et al ( 2023 ) examined the relationship between a range of day-to-day PTSD symptoms variability and sleep in non-treatment-seeking trauma-exposed young adults, using both objective and subjective measures. Exploratory analyses indicated that sex moderated the bi-directional relationships between night-time sleep and day-time PTSD symptoms, with longer sleep onset latency and lower sleep efficiency being related to worse PTSD symptoms the next day in women, but not in men.…”
Section: In This Special Issuementioning
confidence: 99%
“…Specifically, decreases in amygdala nuclei volumes have been reported to be associated with symptoms of PTSD ( 21 , 24 , 29 ). Reduced grey matter volume in limbic brain regions including the amygdala are correlated with sleep disturbances (insomnia and nightmares) in patients with PTSD ( 30 ), which may contribute to symptom severity ( 31 , 32 ). Analysis of links between BLA and centrocorticomedial complex volumes with PTSD symptom severity in 47 young survivors from the 2011 Norwegian terror attack revealed an inverse relationship between symptom severity and amygdala nuclei volume 24–36 months post-trauma ( 21 ), supporting associations between these factors and PTSD.…”
Section: Observationsmentioning
confidence: 99%